2017
DOI: 10.18203/2320-1770.ijrcog20171033
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate the causes of stillbirths according to the ReCoDe classification

Abstract: Background: Foetal death or stillbirth is a major obstetrical complication and a devastating experience for the pregnant patients and relatives. Worldwide an estimate of at least 3.2 million stillbirths occurs each year. There are intensified demands on medical, political and epidemiological ground for proper determination and classification of causes of perinatal death. The aim of this study was to test a new classification system- Re. Co. De. Classification (Relevant Condition at Death) for stillbirths to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…16 The classification systems used in the study was ReCoDe in ordered to cut down the rates of unexplained stillbirths.…”
Section: I2) No Information Availablementioning
confidence: 99%
See 1 more Smart Citation
“…16 The classification systems used in the study was ReCoDe in ordered to cut down the rates of unexplained stillbirths.…”
Section: I2) No Information Availablementioning
confidence: 99%
“…In Parihar et al study, fetal lethal anomaly formed thelargest group (8.14%). 16 Strengths and Limitations: MIMS is a large tertiary care referral centre probably a lone referral centre for all high risk obstetric cases catering to a large rural population. MIMS also has significant number of booked cases that have regular obstetric care.…”
Section: I2) No Information Availablementioning
confidence: 99%
“…[7] Similarly, cause of stillbirths was identifiable in almost 90% of the cases in studies using ReCoDe classification system. [13,14] Intrauterine growth restriction was the major cause of stillbirths (22%) followed by congenital anomalies (15%) and hypertensive disorders of pregnancy (14%) in our study. Similar observation was made in studies using ReCoDe classification system.…”
Section: Discussionmentioning
confidence: 60%
“…Congenital anomalies as the cause of stillbirth were found in 15% of our cases. Other studies also reported slightly lower figures [11][12][13][14]16]. Congenital anomalies diagnosed were neural tube defects (anencephaly, hydrocephalus), cardiac anomalies, duodenal atresia, gastrochiasis all of which could have been diagnosed early in gestation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation